1995
DOI: 10.1007/bf00033625
|View full text |Cite
|
Sign up to set email alerts
|

Chironomid community structure deduced from larvae and pupal exuviae of a chalk stream

Abstract: Species abundances of Chironomidae (Insecta: Diptera) have often been excluded from studies of benthic river communities because of difficulties associated with sampling and identifying larvae . Chironomid pupal exuviae are easier to collect and identify and could be used to determine community structure if shown to be representative of local larval assemblages . Larvae were sampled along a 20 m chain secured over mid-channel gravels, upstream of two collection points for pupal exuviae . Proportional taxa abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 27 publications
1
17
0
2
Order By: Relevance
“…Some examples of this disparity are : Wilson & Bright (1973) took 200 exu viae in the River Rhine as well as Ruse (1993Ruse ( , 1995 in the Pang river. In the River Meuse, Kuijpers et al (1992) as well as Evrard (1996) identified 300 pupal exuviae whereas Frantzen (1992) in the Lower Rhone river and Gendron & Laville (1995) in a 4 th order sec tion of the River Aude, showed that 500 exuviae was best.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Some examples of this disparity are : Wilson & Bright (1973) took 200 exu viae in the River Rhine as well as Ruse (1993Ruse ( , 1995 in the Pang river. In the River Meuse, Kuijpers et al (1992) as well as Evrard (1996) identified 300 pupal exuviae whereas Frantzen (1992) in the Lower Rhone river and Gendron & Laville (1995) in a 4 th order sec tion of the River Aude, showed that 500 exuviae was best.…”
Section: Sampling Methodsmentioning
confidence: 99%
“…Using chironomids collected from a large river, Fesl (2002) reported that the observed communities did not fit the various niche-oriented models including the geometric series, whereas the distribution of functional feeding groups in chironomids fitted the random fraction model. In contrast, Ruse (1995) found that the abundance patterns of larval and pupal chironomids from a chalk stream were best described by a log series model. Alternatively, Dimitriadis and Cranston (2007) studied estuarial systems, where abundance patterns of chironomid communities fitted geometric series.…”
Section: Introductionmentioning
confidence: 79%
“…Futher research is required in checking how the subdivision pattern of niche will occur in aquatic conditions in this study. In fact, a wide variety of SAD models have been proposed including random fraction or assortment (Tokeshi, 1990(Tokeshi, , 1993(Tokeshi, , 1999Fesl, 2002), log series (Ruse, 1995), geometric series (Dimitriadis and Cranston, 2007). This indicated that chironomid communites would show diverse SAD patterns in adapting to competition for resources and for environmental disturbances at study sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations